BEYOND BURNOUT: A META-ANALYSIS OF PSYCHOSOCIAL SAFETY CLIMATE AND ITS IMPACT ON EMPLOYEE WELL-BEING AND ORGANIZATIONAL PERFORMANCE - Maidawati; Ramon Zamora; Oktavianti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study presents a meta-analysis examining the impact of Psychosocial Safety Climate (PSC) on employee well-being and organizational performance. Drawing on a systematic review of empirical studies, the research synthesizes evidence to determine the strength and consistency of relationships between PSC, burnout, stress, engagement, and key performance indicators such as productivity and turnover. The findings reveal that PSC is a strong predictor of improved psychological health, significantly reducing burnout and stress while enhancing job satisfaction and engagement. Additionally, PSC demonstrates a positive relationship with organizational performance, including increased productivity and reduced absenteeism. The analysis identifies job demands and resources as key mediating mechanisms, while leadership, industry context, and work arrangements act as important moderating factors. The results highlight the limitations of individual-focused interventions and emphasize the value of organizational-level approaches. Overall, PSC is identified as a strategic lever for promoting sustainable well-being and performance in modern workplaces.